2013
DOI: 10.1093/gji/ggt396
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the thermal aureole of a magmatic intrusion in immature to mature sediments: a case study in the East Greenland Basin (73°N)

Abstract: The Cretaceous and Triassic argillaceous rocks from the passive margin of Greenland have been investigated in order to detect the thermal aureole of magmatic intrusions, ranging from metric dyke to kilometric syenite pluton. Rock-Eval data (Tmax generally <468 • C), vitrinite reflectance data (R0 < 0.9 percent) and illite cristallinity data (ICI > 0.3), all indicate a maximum of 5km burial for the argillaceous rocks whatever the distance to an intrusion. The K-Ar dating of the clays <2µm fraction suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In addition, pyrrhotite may also be present closer to the intrusion contact where palaeotemperatures were above 220°C, (Katz et al, 1998). In the East Greenland volcanic margin, Aubourg et al (2014) reported the occurrence of >1 μm pyrrhotite, characterized by a well‐developed Besnus transition at 35K, in sediments sampled in the thermal aureole of a magmatic intrusion. Therefore, the pyrrhotite detected in our samples is most likely related to contact metamorphism where palaeotemperature exceeded 250°C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pyrrhotite may also be present closer to the intrusion contact where palaeotemperatures were above 220°C, (Katz et al, 1998). In the East Greenland volcanic margin, Aubourg et al (2014) reported the occurrence of >1 μm pyrrhotite, characterized by a well‐developed Besnus transition at 35K, in sediments sampled in the thermal aureole of a magmatic intrusion. Therefore, the pyrrhotite detected in our samples is most likely related to contact metamorphism where palaeotemperature exceeded 250°C.…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale is based on the principle that the formation of new minerals carrying a remanent chemical magnetization reflects the thermal history of a rock (e.g. Aubourg, Techer, Geoffroy, Clauer, & Baudin, 2014; Kars, Aubourg, Pozzi, & Janots, 2012). In particular, changes in magnetic assemblages are often the result of precipitation of iron that is released during the alteration of pyrite (Brothers, Engel, & Elmore, 1996) or clays (Katz, Elmore, & Engel, 1998) during early diagenesis (Roberts, 2015; Roberts & Weaver, 2005; Rowan & Roberts, 2006; Rowan, Roberts, & Broadbent, 2009), thermal maturation of sedimentary rocks (Banerjee, Elmore, & Engel, 1997) and increasing burial (Aubourg, Pozzi, & Kars, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sedimentary basins, the occurrence of pyrrhotite may be an indication of burial temperatures exceeding 200 • C (Crouzet et al, 2001). Several studies reported the formation of pyrrhotite in thermal aureoles of magmatic intrusions (Gillett, 2003;Wehland et al, 2005;Ledevin et al, 2012;Aubourg et al, 2014). At Site U1546, pyrite is present down to 350 m b.s.f.…”
Section: Metamorphic Aureole Characteristicsmentioning
confidence: 99%